Drawing on LGB Identity to Encourage Participation and Disclosure of Sexual Orientation in Surveys. Issue 1 (2nd January 2019) - Stange, Mathew; Smyth, Jolene D.; Olson, Kristen
ABSTRACT: This paper reports an experiment that tested how three survey cover designs – images of traditional families and individuals displaying themselves in typical gender ways; images of lesbian, gay, and bisexual (LGB) and heterosexual individuals and families; and no cover images – affected LGB people's participation and disclosure of LGB identity and non-LGB people's participation. Analyses showed the LGB-inclusive cover led to significantly more LGB respondents than the other designs, without significantly affecting the demographic, political, and religious makeup of the completed sample. We discuss what these findings mean for addressing two challenges: getting LGB people to respond to surveys and to disclose their LGB identity.